Truncated NS1 Influenza A Virus Induces a Robust Antigen-Specific Tissue-Resident T-Cell Response and Promotes Inducible Bronchus-Associated Lymphoid Tissue Formation in Mice - Anna-Polina Shurygina; Marina Shuklina; Olga Ozhereleva; Ekaterina Romanovskaya-Romanko; Sofia Kovaleva; Andrej Egorov; Dmitry Lioznov; Marina Stukova (Vaccines)
Background: Influenza viruses with truncated NS1 proteins show promise as viral vectors and candidates for mucosal universal influenza vaccines. These mutant NS1 viruses, which lack the N-terminal half of the NS1 protein (124 a.a.), are unable to antagonise the innate immune response. This creates a self-adjuvant effect enhancing heterologous protection by inducing a robust CD8+ T-cell response together with immunoregulatory mechanisms. However, the effects of NS1 modifications on T-follicular helper (Tfh) and B-cell responses remain less understood. Methods: C57bl/6 mice were immunised intranasally with 10 μL of either an influenza virus containing a truncated NS1 protein (PR8/NS124), a cold-adapted influenza virus with a full-length NS1 (caPR8/NSfull), or a wild-type virus (PR8/NSfull). Immune responses were assessed on days 8 and 28 post-immunisation by flow cytometry, ELISA, and HAI assay. Results: In this study, we demonstrate that intranasal immunisation with PR8/NS124 significantly increases tissue-resident CD4+ and CD8+ T cells in the lungs and activates Tfh cells in regional lymph nodes as early as day 8 post-immunisation. These effects are not observed in mice immunised with caPR8/NSfull or PR8/NSfull. Notably, PR8/NS124 immunisation also leads to the development of inducible bronchus-associated lymphoid tissue (iBALT) in the lungs by day 28, characterised by the presence of antigen-specific Tfh cells and GL7+Fas+ germinal centre B cells. Conclusions: Our findings further underscore the potential of NS1-truncated influenza viruses to drive robust mucosal immune responses and enhance vaccine efficacy.